Merdeka Belajar Penerapan Ajaran Ki Hajar Dewantara “Merdeka Belajar” Dalam Pembelajaran IPA Sekolah Dasar - Diah Wasis Priyono; Priyadi Priyadi; Ana Fitrotun Nisa; Bonifatius Sigit Yuniharto (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
Elementary science learning is intended to provide direct experience in developing students' abilities so that they can explore and understand the natural surroundings scientifically. Freedom to learn means that educators and their students have the freedom to innovate, the freedom to learn independently and creatively. This study aims to describe the application of independent learning according to the teachings of Ki Hajar Dewantara in elementary science learning and the constraints of implementing independent learning in science learning at SDN 1 Sidogede, Prembun District. This type of research is descriptive qualitative research with a case study research strategy. Data collection techniques in this study are observation, interviews and documentation. The data analysis technique used is source triangulation and method triangulation which includes data collection, data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that SDN 1 Sidogede will carry out learning based on three indicators from the Teachings of Ki Hajar Dewantara, namely students are comfortable in the learning process, students have a high social conscience and students are independent or free in determining the talents and interests they like. The obstacles are that when learning takes place it cannot run optimally because of signal constraints, students are shy and insecure, low grade students are less able to concentrate like upper classes, and limited funds to bring in trainers who can help students develop their talents and interests.